Hydration Status and Glycemic Indices of Patients with Type 2 Diabetes Mellitus and HIV Comorbidities in South-South Nigeria - Ikpe, Itoro Lawrence; Ekpenyong, Christopher E.; Udokang, Nsikak E.; Inwang, Uduak A. (International Journal of Research in Interdisciplinary Studies, 2025)
Recently there have been an increasing trend of HIV positive patients surviving longer due to increased availability and compliance with antiretroviral therapy. Some of these patients tend to develop type 2 diabetes mellitus (T2DM) as a result of exposure to certain antiretroviral drugs as well as increasing age of the patients. HIV and T2DM could increase the risks of dehydration in these patients. This study was designed to assess the hydration status of patients having HIV and T2DM comorbidities in Akwa Ibom State, South-South Nigeria. In this study 128 participants aged 18 to 59 years were recruited consecutively from December 2023 to May 2024 from designated hospitals in Akwa Ibom state and grouped into normal, diabetic, HIV and diabetic/HIV with each group made up of 32 individuals. Blood samples were taken for on-the-spot blood glucose estimation, glycated haemoglobin, haemoglobin concentration, serum electrolytes, urea and creatinine. Urine was collected for urinalysis. Serum osmolarity and anion gap were calculated. Blood urea nitrogen concentration as well as blood urea nitrogen/creatinine ratio were also determined. The results showed a significantly higher mean chloride level in the normal and diabetic groups compared to others and a higher bicarbonate level in the diabetic group. Urea and creatinine levels were significantly higher in the diabetic and diabetic+HIV groups when compared with others. Serum calcium was significantly higher in the diabetic and HIV groups compared to others. BUN and BUN/creatinine ratio were significantly higher in the diabetic only group compared to others with serum anion gap, osmolarity, FBS/RBS and HBA1C levels being significantly higher in the diabetic group compared to others. It is concluded that T2DM increased the risk of dehydration which is exacerbated by diabetic/HIV comorbidity.